Influencing factors that determine capital structure decisions: A review from the past to present - Prince Yeboah Boateng; Baba Issah Ahamed; Michael Gift Soku; Salomey Osei Addo; Lexis Alexander Tetteh (Cogent Business & Management, 2022)
This review study seeks to assess the state of determinants of corporate capital structure over the last 7~years to aid discover gaps as opportunity for further research. The review used a sample of 68 published journal articles in divers high-ranked journals spanning the years 2014-2020. The review study considered criteria for inclusion and exclusion of the published journal articles. Findings from the review study reveal that study on capital structure determinants focuses largely on quantitative research than qualitative research and mixed research. Again, capital structure determinants research concentrates more on nonfinancial sector as against the financial sector. However, firm-level study has been realized to dominate the level of analysis space in comparison with industry-level, country-level and synthesis-level studies. Moreover, estimation technique centered greatly on regression analysis model in relation to others. Notwithstanding, the study observed that the pecking order theory is the most adopted in addressing issues of capital structure determinants. The authors provide analysis on research methodology approach and geographical region coverage as being part of addition made to reviews in this study area. Recommendations have been made for future review in the field of capital structure determinants.
Keywords: 650; Capital structure determinants; information asymmetry theory; literature review; Modigliani and Miller theory; pecking order theory; trade-off theory